2019
DOI: 10.1109/tip.2019.2895542
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Multi-View Surface Normal Estimation Using Affine Correspondences

Abstract: An optimal, in the least squares sense, method is proposed to estimate surface normals in both stereo and multi-view cases. The proposed algorithm exploits exclusively photometric information via affine correspondences and estimates the normal for each correspondence independently. The normal is obtained as a root of a quartic polynomial. Therefore, the processing time is negligible. Eliminating the outliers, we propose a robust extension of the algorithm that combines maximum likelihood estimation and iterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Application: surface normal estimation using affine correspondences. We applied the multi-view least-squares optimal method from [8] to estimate surface normals from the extracted and corrected LAFs. The used sequences from the Strecha dataset are fountain -p11, herzjesus-p8 and herzjesus-p25 since those are the only ones with publicly available ground truth 3D point cloud.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Application: surface normal estimation using affine correspondences. We applied the multi-view least-squares optimal method from [8] to estimate surface normals from the extracted and corrected LAFs. The used sequences from the Strecha dataset are fountain -p11, herzjesus-p8 and herzjesus-p25 since those are the only ones with publicly available ground truth 3D point cloud.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, if the cameras are calibrated, the normal can be unambiguously estimated from a single correspondence [15]. Multiple-view normal estimation [8,12] is also possible. Pritts et al [26,27] showed that the radial distortion parameters can be retrieved, as well.…”
Section: Introductionmentioning
confidence: 99%
“…Ivan Eichhardt and Levente Hajder have a series of works exploiting the local affine correspondences for surface normals estimation [24]…”
Section: Surface Normals Estimationmentioning
confidence: 99%
“…A feature-based SfMapproach with a novel approach that refines motion (camera parameters and poses) and structure (both 3D points and surface normals) demonstrates the use of ACs for 3D reconstruction. Related publications are [6,1,12,13,14,16,17,18,19,4].…”
Section: Main Contributionsmentioning
confidence: 99%